2016
DOI: 10.1515/jpem-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Maturity onset diabetes of youth (MODY) in Turkish children: sequence analysis of 11 causative genes by next generation sequencing

Abstract: This is the first study including molecular studies of 11 MODY genes in Turkish children. GCK is the most frequent type of MODY in our study population. Very high frequency of novel mutations (42%) in our study population, supports that in heterogenous disorders like MODY sequence analysis provides rapid, cost effective and accurate genetic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
4
23
2
Order By: Relevance
“…In these populations, NEUROD1 mutations range from low frequencies as in Poland (0.64%; Szopa et al, ) to high frequencies as in India (7.14%; Chapla et al, ). In our study, we found a frequency of 4%, similar to that observed in Turkish (4.65%; Ağladıoğlu et al, ; Table ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In these populations, NEUROD1 mutations range from low frequencies as in Poland (0.64%; Szopa et al, ) to high frequencies as in India (7.14%; Chapla et al, ). In our study, we found a frequency of 4%, similar to that observed in Turkish (4.65%; Ağladıoğlu et al, ; Table ).…”
Section: Discussionsupporting
confidence: 90%
“…In 1999, mutations in NEUROD1 were associated to early onset type 2 diabetes mellitus (DM) in two European descendent families inherited in an autosomal dominant fashion for the first time (Malecki et al, ), being further classified as maturity‐onset diabetes of the young type 6 (MODY6; OMIM #606394) (Fajans, Bell, & Polonsky, ). Almost 20 years after the first report, only a few families in Europe (Ağladıoğlu et al, ; Gonsorčíková et al, ; Kristinsson et al, ; Szopa et al, ) and Asia (Ang et al, ; Chapla et al, ; Doddabelavangala Mruthyunjaya et al, ; Horikawa et al, ; Liu et al, ) had shown mutations in NEUROD1 as the cause of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have identified a novel heterozygous G-to-A substitution at 278 position (c.278G>A) that changes cysteine to tyrosine amino acid (p.C93Y) in exon 3 in HNF4A, which leads to MODY Type I. Flanagan et al (8) have reported a different de novo HNF4A mutation at the same position (p.C93S, c.278 G>C) leading to a diazoxide responsive hyperinsulinemic hypoglycemia that was diagnosed within the first week of life in a patient born with macrosomia (4.100 gr). Our group (9) did not detect HNF4A mutations in 42 children diagnosed with MODY, but Ağladıoğlu et al (10) analyzed 43 patients with MODY and identified two cases with the same heterozygous HNF4A mutations. One of the cases had a missense mutation (c.416C>T), which is associated with Type II diabetes mellitus in the HGMD.…”
Section: Discussionmentioning
confidence: 73%
“…Of all MODY cases, 20-50% are caused by GCK and HNF1A, approximately 10% are from a mutation of HNF4A or HNF1B (3). Studies from our country reported that GCK is the most common subtype (9)(10)(11). In the present study, we have identified a novel heterozygous G-to-A substitution at 278 position (c.278G>A) that changes cysteine to tyrosine amino acid (p.C93Y) in exon 3 in HNF4A, which leads to MODY Type I. Flanagan et al (8) have reported a different de novo HNF4A mutation at the same position (p.C93S, c.278 G>C) leading to a diazoxide responsive hyperinsulinemic hypoglycemia that was diagnosed within the first week of life in a patient born with macrosomia (4.100 gr).…”
Section: Discussionmentioning
confidence: 92%
“…Heterozygous loss‐of‐function mutations in NEUROD1 have been reported as a very rare cause of maturity‐onset diabetes of the young (MODY) and are associated with increased risk of adult onset diabetes . Homozygous mutations in the NEUROD1 gene are extremely rare with only 2 cases of PNDM and associated neurological abnormalities due to homozygous frameshift mutations reported …”
Section: Introductionmentioning
confidence: 99%